2016
DOI: 10.1007/978-3-319-44902-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Responsibilities and Challenges of Product Owners at Spotify - An Exploratory Case Study

Abstract: In Scrum, the Product Owner (PO) role is crucial for the team to be successful in developing useful and usable software. The PO has many responsibilities and challenges, including being the link between customers, other stakeholders and their development teams. This exploratory case study conducted at the software development company Spotify focuses on POs three responsibilities: a) Identification of customers, b) Estimation of value of their teams' work and c) Forming a vision for the product. Additionally, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…They described Product Owner as a very difficult role since the Product Owner's success depends on many factors such as organizational culture, project type, management approach, and the interaction within the team that is developing the product. A case study at Spotify was done by Kristinsdottir et al [39], focusing on the Product Owners' responsibilities and challenges. There was no explicit agreement among the interviewees on the actual daily responsibilities, as there were many tasks to juggle each day.…”
Section: Product Owner Rolementioning
confidence: 99%
See 2 more Smart Citations
“…They described Product Owner as a very difficult role since the Product Owner's success depends on many factors such as organizational culture, project type, management approach, and the interaction within the team that is developing the product. A case study at Spotify was done by Kristinsdottir et al [39], focusing on the Product Owners' responsibilities and challenges. There was no explicit agreement among the interviewees on the actual daily responsibilities, as there were many tasks to juggle each day.…”
Section: Product Owner Rolementioning
confidence: 99%
“…There was no explicit agreement among the interviewees on the actual daily responsibilities, as there were many tasks to juggle each day. "Some respondents commented that they needed to have one foot in the daily work and one foot in the future and lead people to work on the right things at any given moment" [39] (p. 13). The study confirmed that Product Owner is a complex role with both inward-and outward-facing responsibilities.…”
Section: Product Owner Rolementioning
confidence: 99%
See 1 more Smart Citation
“…Although Scrum teams are mentioned several times by scholars, team dynamics have rarely been the focus of an investigation. Rather than within the team, the research looked into the relationship between the team and the stakeholders, such as the Product Owner [20], and across teams [21].…”
Section: Related Workmentioning
confidence: 99%
“…Several researcher identified communication to be of particular importance in the development process (cf. previous studies [18][19][20][21][22][23][24][25] ). However, we did not find a publication investigating the communication of Product Owners in detail.…”
Section: Related Workmentioning
confidence: 99%